2008
DOI: 10.1136/oem.2007.038430
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors at work and risk of depression: a systematic review of the epidemiological evidence

Abstract: This review provides consistent findings that perception of adverse psychosocial factors in the workplace is related to an elevated risk of subsequent depressive symptoms or major depressive episode; however, methodological limitations preclude causal inference. Studies implementing objective measures of job stressors or independent outcome ascertainment are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
603
6
39

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(695 citation statements)
references
References 40 publications
47
603
6
39
Order By: Relevance
“…The second factor, person-oriented, was embodied by intellectual disturber and physical disturber; therefore, these participants perceived stress as a physical and an intellectual personal disturber. These results are in line with previous studies (Bonde, 2008;Cox et al, 2000;Jacobs et al, 2007;Kivimäki et al, 2003;Rafferty & Griffin, 2006;Siegrist, 1996). If prolonged, they can have adverse effects on physical and mental health (Kivimäki et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…The second factor, person-oriented, was embodied by intellectual disturber and physical disturber; therefore, these participants perceived stress as a physical and an intellectual personal disturber. These results are in line with previous studies (Bonde, 2008;Cox et al, 2000;Jacobs et al, 2007;Kivimäki et al, 2003;Rafferty & Griffin, 2006;Siegrist, 1996). If prolonged, they can have adverse effects on physical and mental health (Kivimäki et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In all of these instances, the magnitude of the associations we investigated would be inflated. However, this issue has been much debated (Bonde, 2008), and a recent meta-analysis using populations without common mental disorders at the inception of the study concluded that associations between job strain and subsequent poor mental health could not be explained by response bias (Stansfeld and Candy 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Most studies of psychosocial risk factors do not measure dimensions such as emotional demands because they are not part of the very popular job strain model [23].…”
Section: Discussionmentioning
confidence: 99%